A identidade alegórica em Dexter: serial killers como categoria da identidade pós-moderna - CASTRO, Fábio Fonseca de (Centro Interdisciplinar de Semiótica da Cultura e da Mídia, 2022)
The article discusses, regarding the television serie Dexter, the role of serial killer figure in postmodern culture. That show, which tells the story of a serial killer whose trouble is to kill serial killeres, produces a reflexivity about the condition of identity of the contemporary individuos. We believe that the serial killer allegorizes the historical condition of the contemporary personality through an evocation of the social dynamics of serial consumption, one generalized social practice in contemporary society and through which social status and identity are resignified and typified.